Implementation of a Smart Home Doorbell System for Guest Identification Using ESP32-CAM and IoT-Based Telegram Chatbot Integration - Syavira, Raihan (Journal of Technology and Computer, 2025)
This study develops a SmartHome system integrated with a doorbell that automatically identifies visitors using ESP32-CAM and sends notifications to homeowners through a Telegram chatbot. The system enables remote visitor monitoring and voice-based responses via a speaker. It integrates ESP32-CAM, a wireless doorbell, DFPlayer Mini MP3, and a speaker. When the doorbell is pressed, the ESP32-CAM captures the visitor’s image and sends it to Telegram. The homeowner can then issue commands to play pre-recorded voice responses stored in a microSD card. Testing results demonstrate that the system functions effectively, providing enhanced home security and convenience. The integration between hardware, Arduino IDE software, and internet-based communication shows reliable performance. This system offers an innovative approach to SmartHome applications by combining IoT-based visitor detection with real-time communication.